The South African anaphora: the development of the anaphora of the South African Eucharistic rite - Hinchliff, Peter Bingham (Rhodes University, Faculty of Divinity, Department of Divinity, 1958)
The Prayer Book of the Church of England reached South Africa as a part of the establishment of the British Administration at the Cape. In its new environment it obviously required some revision. The Book of 1662 reflected the political and social conditions of its time. lt was designed for a Church not immediately concerned with missionary work amongst heathen peoples but directly established under the Crown. The circumstances of a Church in the colonies, particularly when the colonies became self-governing, required some modernisation of language, some omission and adaptation of old prayers and some addition of new ones. Yet the Church appears to have been wary of attempting anything more than this, and it was especially reluctant to make any revision which might imply a doctrinal change. The consecration prayer in the liturgy -'our incomparable liturgy' - was particularly sacrosanct by virtue of long use and the accretion of sentimental associations. Revision of this part of the book would naturally be slow and hesitant and this is the revision with which we are concerned - the most interesting and important part of the history of the South African Prayer Book. Chapter 1, p. 6.
Keywords: Church of the Province of South Africa -- Book of common prayer -- History -- Sources; Eucharistic prayers; Eucharistic prayers -- Anglican; Communion; Anglican Communion -- Liturgy -- History -- Sources; Anglican Communion -- South Africa -- Liturgy -- History -- Sources